The Effect Of Perceived Usefulness, Perceived Ease Of Use, And Perceived Security On E-Wallet Usage Interest With Trust As An Intervening Variable (Case Study Of Makassar State University) - Nabila Lutfiah Amiruddin; Muhammad Ichwan Musa; Hety Budiyanti (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study examines the effect of perceived usefulness, perceived ease of use, and perceived security on students’ interest in using e-wallets, with trust functioning as an intervening variable. The research was conducted at Makassar State University using a quantitative causal approach. A total of 50 respondents were selected through purposive sampling, limited to students actively using e-wallets for at least the last six months. Data were analyzed using multiple linear regression with SPSS 30. Descriptive statistics show consistent perceptions among respondents, with perceived usefulness (Min = 25; Max = 40; SD = 3.608), perceived ease of use (Min = 23; Max = 40; SD = 3.678), and perceived security (Min = 24; Max = 40; SD = 3.645). Meanwhile, intention to use e-wallets shows higher variation (Min = 29; Max = 51; SD = 4.688). Regression results demonstrate that perceived usefulness (t = 4.244; B = 0.634; Sig. = 0.003), perceived ease of use (t = 5.421; B = 0.674; Sig. = 0.000), and perceived security (t = 5.954; B = 0.676; Sig. = 0.000) significantly influence usage interest. Perceived ease of use provides the strongest influence. The F-test (F = 80.533; Sig. = 0.000) further confirms that the overall model significantly predicts e-wallet usage intention. Additionally, trust acts as an intervening variable that strengthens the influence of perceived security on usage interest, indicating that higher trust enhances adoption behavior. The study concludes that improving usefulness, ease of use, and security along with building user trust is essential for increasing students’ e-wallet adoption.